Cyclooctatetraenide-based single-ion magnets featuring bulky cyclopentadienyl ligand. Issue 35 (30th August 2022) - Korzyński, Maciej Damian; Bernhardt, Moritz; Romankov, Vladyslav; Dreiser, Jan; Matmon, Guy; Pointillart, Fabrice; Le Guennic, Boris; Cador, Olivier; Copéret, Christophe
Abstract : Application of steric control principles allows for simplification of the magnetic behavior of an iconic single-ion magnet architecture as well as the preparation of its previously inaccessible representative. Abstract : We report a family of organometallic rare-earth complexes with the general formula (COT)M(Cp ttt ) (where (COT) 2− = cyclooctatetraenide, (Cp ttt ) − = 1, 2, 4-tri( tert -butyl)cyclopentadienide, M = Y(iii ), Nd(iii ), Dy(iii ) and Er(iii )). Similarly to the prototypical Er(iii ) analog featuring pentamethylcyclopentadienyl ligand (Cp*) −, (COT)Er(Cp ttt ) behaves as a single-ion magnet. However, the introduction of the sterically demanding (Cp ttt ) − imposes geometric constraints that lead to a simplified magnetic relaxation behavior compared to the (Cp*) − containing complexes. Consequently, (COT)Er(Cp ttt ) can be viewed as a model representative of this organometallic single-ion magnet architecture. In addition, we demonstrate that the increased steric profile associated with the (Cp ttt ) − ligand permits preparation, structural characterization and interrogation of magnetic properties of the early-lanthanide complex, (COT)Nd(Cp ttt ). Such a mononuclear derivative could not be obtained when a (Cp*) − ligand was employed, a testament to larger ionic radius of this early lanthanide ion.